Answer: x = -2
Explanation
10x + 30-(-9x-4)=x5+3
19
x
+
34
=
x
−
5
+
3
19x+34=x-5+3
Add
−
5
-5 and
3
3.
19
x
+
34
=
x
−
2
19x+34=x-2
Move all terms containing
x
x to the left side of the equation.
Tap for fewer steps...
Subtract
x
x from both sides of the equation.
19
x
+
34
−
x
=
−
2
19x+34-x=-2
Subtract
x
x from
19
x
19x.
18
x
+
34
=
−
2
18x+34=-2
Move all terms not containing
x
x to the right side of the equation.
Tap for fewer steps...
Subtract
34
34 from both sides of the equation.
18
x
=
−
2
−
34
18x=-2-34
Subtract
34
34 from
−
2
-2.
18
x
=
−
36
18x=-36
Divide each term by
18
18 and simplify.
Tap for fewer steps...
Divide each term in
18
x
=
−
36
18x=-36 by
18
18.
18
x
18
=
−
36
18
18x18=-3618
Reduce the expression by cancelling the common factors.
Tap for more steps...
x
=
−
36
18
x=-3618
Divide
−
36
-36 by
18
18.
x
=
−
2